Compulsive Hoarding Symptoms and the Role of Mindfulness Skills During Social Distancing for the COVID-19 Pandemic: An Exploratory Survey - Marazziti, Donatella; Pozza, Andrea; Mucci, Federico; Dettore, Davide (Frontiers in Psychiatry, 2021)
People reporting compulsive hoarding symptoms (CHS) have lower mindfulness skills than those without such symptoms. Mindfulness skills can have the role of a protective buffer against stressful periods. The quarantine imposed to contain the COVID-19 spread had a negative impact on daily habits and healthy behaviors (including social interactions). An increased attachment to objects might be one of the under-recognized psychological consequences of these difficult times, yet no study focused on CHS. Through an online survey in men who were on quarantine during the pandemic, this exploratory survey examined the prevalence of men reporting CHS during this period and explored the role of mindfulness skills on CHS controlling for anxious-depressive/stress symptoms. Forty-three men from the general population completed the Obsessive Compulsive Inventory-Revised (OCI-R), Cognitive and Affective Mindfulness Scale-Revised (CAMS-R) and Depression Anxiety Stress Scales-21 (DASS-21). Twenty-eight percent reported CHS. No differences on the scores of the questionnaires emerged between men with and without CHS, except on CAMS-R Attention scores. In a logistic regression analysis lower CAMS-R Attention scores predicted CHS (β = −0.34, p = 0.03). This is the first, yet preliminary investigation on CHS during quarantine. The prevalence of CHS appears higher than the rates (4%) reported in the last years before the COVID-19 outbreak. Perhaps people showed more intense hoarding tendencies during quarantine/social distancing, and this pattern should be monitored. Larger samples, longitudinal designs and clinician-rated instruments are needed to support or not our findings.